2005
DOI: 10.1089/acm.2005.11.407
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Electrical Acupoint Stimulation Versus Ondansetron in the Prevention of Postoperative Vomiting Following Pediatric Tonsillectomy

Abstract: Application of TEAS on sedated children is an easy, painless, reliable and effective method for the prophylaxis of postoperative retching and vomiting in pediatric tonsillectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…These nonpharmacological techniques are more effective than placebo for preventing PONV within 6 h postoperatively [106]. In a previous report by Kabalak et al [60], transcutaneous electrical acupoint stimulation was effective for the prevention of POV in children who underwent tonsillectomy, and its antiemetic efficacy was the same as ondansetron 0.15 mg kg -1 . By contrast, Shenkamnn et al [61] and Rusy et al [62] demonstrated that perioperative acupressure and acupuncture did not reduce the incidence of POV ( Table 5).…”
Section: Cupressure and Acupuncturementioning
confidence: 98%
“…These nonpharmacological techniques are more effective than placebo for preventing PONV within 6 h postoperatively [106]. In a previous report by Kabalak et al [60], transcutaneous electrical acupoint stimulation was effective for the prevention of POV in children who underwent tonsillectomy, and its antiemetic efficacy was the same as ondansetron 0.15 mg kg -1 . By contrast, Shenkamnn et al [61] and Rusy et al [62] demonstrated that perioperative acupressure and acupuncture did not reduce the incidence of POV ( Table 5).…”
Section: Cupressure and Acupuncturementioning
confidence: 98%
“…ES was primarily applied for the prevention or treatment of nausea and vomiting, except for one study that used LS for this purpose. TEAS was the main method used for preventing nausea and vomiting: we retrieved nine articles on TEAS,96, 97, 98, 99, 100, 101, 102, 103, 104 two on EA,105, 106 and one on LS 107 . A total of 830 individuals who received TEAS experienced an effect on prevention, reduction, or treatment of postoperative nausea and vomiting and nausea or vomiting.…”
Section: Resultsmentioning
confidence: 99%
“…TENS application at acupuncture points has increased in recent years, as it is a non-invasive method of stimulating acupuncture points. Ni et al demonstrated that TENS stimulation at the P6 acupoint resulted in a decreased inflammatory response following pediatric cardiac surgery [22], while Kabalak et al showed that TENS application resulted in decreased emesis following tonsillectomy in a pediatric population [23]. Our previous study demonstrated the safety of TENS in neonates, [9] but no other studies have examined the effectiveness of NESAP against heelstick pain in infants.…”
Section: Discussionmentioning
confidence: 97%